ANALYSIS OF THE COST OF ORGANIZING THE HAJJ WORSHIP (BPIH) - Nursanita Nursanita; Faris Faruqi (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2024)
Hajj is an obligation on the fifth pillar of Islam where every Muslim who is able or istithoah will go on pilgrimage to Mecca, Saudi Arabia. Indonesia is the largest Hajj congregation but the costs borne by each pilgrim increase every year. This research seeks a solution by dissecting BIPIH using efficiency theory. This research uses a quantitative descriptive approach. Secondary data is used to analyze efficiency. It can be concluded that efficiency can be implemented by the government with a policy of reducing the costs charged to pilgrims to indirect costs, such as health protocols and other costs with the stipulation of the Presidential Decree of the Republic of Indonesia Number 5 of 2022, so that the costs of organizing the Hajj pilgrimage are funded from the current year's benefit value or it is even appropriate to be charged to the APBN considering that the Muslim population is 85% of the population of the Republic of Indonesia.